answersLogoWhite

0


Best Answer

1a+3b

2a+4b=3a +7b

User Avatar

Wiki User

โˆ™ 2012-05-29 21:42:00
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is 1a plus 2a plus 3b plus 4b and what is the answer?
Write your answer...
Submit
Related questions

What is 9a plus 3b-11a-4b?

9a + 3b - 11a - 4b = -2a -b


2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-3+5=3b-1


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


5a squared plus 3b squared plus 2a squared plus 4b squared?

No


5a 2 plus 3b 2 plus 2a 2 plus 4b 2?

20a2b2


What is 1a plus 4b plus 5a plus 3b?

6a+7b. This cannot be simplified anymore unless you know a or b.


What is the simplification for 3a plus 4b-5-a plus 7b plus 3-b?

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2


What is 3a plus 4b - 5 - a?

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5


How do you simplify 3a plus 2b - a plus 4b?

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).


What is 5a - 4b plus 2c - 3b - 6c plus a?

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


What is 3b plus b equal?

4b


-b plus 4b?

equals 3b


What is 8a plus b plus 32a plus 3b?

8a+b+32a+3b=40a+4b


A plus 3b plus 5a plus 4b?

6a+7b


What is 2a-4b?

2a-4b = -2


2a-4b plus 4b-6a equals a plus b?

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1


What is the solution of -7 plus 3b equals 4b-8?

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1


How do you simplify 3b plus b plus 6?

It is: 4b+6


Which expression is equivalent to (3a b)(2a - 4b)?

6a²b - 12ab²


What is 7 plus 4b plus 3b plus 6b plus 5?

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b


How do you factor 2a plus 8b?

2(a + 4b)


What is 3a plus 4b plus 6a plus 3b in algebra?

9a + 7b *remember to look and understand the letters!*


What is the equivalent to 3a plus 4b - -6a - 3b?

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b

Study guides

๐Ÿ““
Create a Study Guide